PERANCANGAN RUMAH SUSUN MAHASISWA UNIVERSITAS TANJUNGPURA DENGAN KONSEP MINIMALIS - Nur Handayani; Irwin Irwin; Muhammad Nurhamsyah (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
Universities located in the city center and far from district locations and areas. Not a few students who migrate to continue their education to tertiary level. This condition certainly requires the existence of temporary housing for overseas students during their education period. Pontianak City is one of the city centers where there is a university, namely, Tanjungpura University. One of the temporary residences that is still rare is the existence of special student flats. These student flats can assist students in helping with temporary housing. This student flat is designed with a minimalist concept which is currently a trend and is in vogue. The purpose of this design is to design student flats that are comfortable with a room atmosphere, space requirements that suit student needs. With several public facilities such as sports venues, shared open spaces, places to relax, places of worship and places to study. The design of student flats prioritizes building functions and efficient space requirements. In achieving this goal, traditional design methods (black box) which in this method is a design method that is carried out spontaneously. Ideas that come from anywhere and at any time according to the designer's imagination spontaneously. Based on background issues and objectives in the design and through some data analysis carried out resulted in a student flat building design with a minimalist concept with a total of 4 floors with private facilities as well as public facilities.